When the intramammary lymph node is the sentinel: a case report - Oliveira, Karla Sorandra Felipe de; Cavalcante, Francisco Pimentel (Mastology, 2018)
Sentinel lymph node biopsy is currently well established in the assessment and determination of axillary status in breast cancer patients. In this scenario, finding intramammary lymph node are not uncommon, but the intramammary sentinel lymph node is rare and has uncertain therapeutic and prognostic significance, which may create difficulties in the management of these patients. Reports in the literature show a worse prognosis when the intramammary sentinel lymph node is compromised by metastasis, because at least 60% of these cases will have concomitant axillary disease. However, the decision on axillary dissection must be determined by the first drainage to the axilla, i.e. by the axillary sentinel node, and when this is not identified, axillary dissection should be recommended due to failure of the method. We report a case of intramammary sentinel lymph node identified and isolated during surgery by the Mastology Service of the General Hospital of Fortaleza, and an updated review of available literature on this subject.